Comparison of Biological, Pharmacological Characteristics, Indications, Contraindications and Adverse Effects of JYNNEOS and ACAM2000 Monkeypox Vaccines - Sultan Ayoub Meo; Abeer A. Al-Masri; David C. Klonoff; Abdullah Nasser Alshahrani; Thamir Al-khlaiwi (Vaccines, 2022)
Human monkeypox is an emerging viral zoonotic disease, that has caused highly distinctive, challenging and threatening problems worldwide. The US Food and Drug Administration (FDA) has given interim authorization for the JYNNEOS and ACAM2000 vaccines for the outbreak of monkeypox 2022. The present study aims to highlight the globally derived evidence about the biological and pharmacological features, indications, contraindications and adverse effects of JYNNEOS and ACAM2000 vaccines. Initially, 82 documents were selected and, finally, 14 fact sheets, documents and international organizations were included. The data were recorded from the World Health Organization (WHO), Centers for Disease Control and Prevention (CDC), Food and Drug Administration (FDA) USA, ISI-Web of Science, PubMed, EMBASE and Scopus. The data revealed that the JYNNEOS vaccine has been recommended to children, adults, females during pregnancy and people of all age groups with a dose of 0.5 mL, and the complete vaccination cost per person is about USD 115. It provides immunogenicity, and the mean titer of neutralizing antibodies was 153.5. However, the ACAM2000 vaccine is contraindicated in infants and pregnant females, and recommended to people over 18 years of age and older, with a single dose of 0.0025 mL, and a cost of about USD 139. ACAM2000 provides immunogenicity, and the mean titer of neutralizing antibodies was 79.3. The JYNNEOS vaccine has mild adverse effects including pain, redness, swelling or itching at the site of the vaccine shot, fever, fatigue, headache, nausea and muscle pain. However, the ACAM2000 vaccine can cause pain, redness, edema, headache, fever, fatigue, muscle pain, body ache, nausea, vomiting, diarrhea, shortness of breath and increased risk of myopericarditis and cardiomyopathy. The evidence supports the view that both vaccines are beneficial, but the overall impact of JYNNEOS is better than that of ACAM2000.